KUALITAS PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH MOKOPIDO KABUPATEN TOLITOLI - Sahdam, Sahdam (Katalogis, 2018)
This research aims to find out the health service quality in government hospital Mokopido Tolitoli. This was a qualitative research where the data obtained and collected through interview with informants selected. The results reveal that health service quality of the hospital viewed from 5 aspects such as reliability, responsiveness, assurance, emphaty, and tangible have not been maximal due to the public still do not feel what is called an excellent service. Fast response service in the hospital still do not appear because there are still many procedures wasting time and the public find difficulties to receive immediate information.